Rare complications of neurofibromatosis 1 diagnosed incidentally in two children - Lazea C; Asavoaie C; Al-Khzouz C; Popa L (Dove Medical Press, 2018)
Cecilia Lazea,1 Carmen Asavoaie,2 Camelia Al-Khzouz,3 Lenuta Popa1 1Department of Pediatrics I, Emergency Clinic Hospital for Children, “Iuliu Hatieganu” University of Medicine and Pharmacy, 2Department of Imaging and Radiology, Emergency Clinic Hospital for Children, 3Medical Genetics Department, Emergency Clinic Hospital for Children, University of Medicine and Pharmacy, Cluj-Napoca, Romania Abstract: Neurofibromatosis 1 (NF1) is an autosomal-dominant disorder with various clinical expressivity and complications. Arterial hypertension may be present in patients with NF1 and is secondary to vasculopathy or pheochromocytoma. We herein describe two children (17 and 4 years old) diagnosed late with NF1 after severe arterial hypertension had been discovered due to pheochromocytoma and middle aortic syndrome. Routine measurement of arterial pressure is mandatory in children with NF1, in order to diagnose the complications of this disease. Keywords: neurofibromatosis, pheochromocytoma, middle aortic syndrome, arterial hypertension, children